Whole-genome sequencing and comparative genome analysis of Xanthomonas fragariae YM2 causing angular leaf spot disease in strawberry - Qiu, Yue; Wei, Fangjun; Meng, Han; Peng, Menglin; Zhang, Jinhao; He, Yilu; Wei, Lanfang; Ahmed, Waqar; Ji, Guanghai (Frontiers in Plant Science, 2023)
Angular leaf spot disease caused by plant pathogenic bacterium Xanthomonas fragariae seriously threatens strawberry crop production globally. In this study, we sequenced the whole genome of X. fragariae YM2, isolated from Yunnan Province, China. In addition, a comparative genome analysis of X. fragariae YM2 was performed with two existing strains of X. fragariae YL19 and SHQP01 isolated from Liaoning and Shanghai, respectively. The results of nanopore sequencing showed that X. fragariae YM2, comprising one single chromosome with a contig size of 4,263,697 bp, one plasmid contig size of 0.39 Mb, a GC content ratio of 62.27%, and 3958 predicted coding genes. The genome of YM2 comprises gum, hrp, rpf, and xps gene clusters and an LPS, which are typical virulence factors in Xanthomonas species. By performing a comparative genomic analysis between X. fragariae strains YM2, YL19, and SHQP01, we found that strain YM2 is similar to YL19 and SHQP01 regarding genome size and GC contents. However, there are minor differences in the composition of major virulence factors and homologous gene clusters. Furthermore, the results of collinearity analysis demonstrated that YM2 has lower similarity and longer evolutionary distance with YL19 and SHQP01, but YL19 is more closely related to SHQP01. The availability of this high-quality genetic resource will serve as a basic tool for investigating the biology, molecular pathogenesis, and virulence of X. fragariae YM2. In addition, unraveling the potential vulnerabilities in its genetic makeup will aid in developing more effective disease suppression control measures.